Utilizing Coffee Husk Biochar as an Effective Adsorbent for Ammonium Removal in Groundwater - Truong, Dai Quyet; Pham, Van Phu; Tran, Le Minh; Nguyen, Tien Vinh (JST: Engineering And Technology For Sustainable Development, 2023)
The study investigated the performance of a novel biochar derived from coffee husks (BCFH) and its alkaline-activated product (BCFH-NaOH) for ammonium removal in the aqueous solution. Several batch experiments were conducted with the synthetic solution to determine the adsorption properties of the biochars. At the initial ammonium concentration of 50 mg/L, the optimal dosage for both materials was 10 g/L, while the ideal pH range was 4–9. The equilibration adsorption time on both materials is within 30 minutes, indicating their high practical applicability. Both the pseudo-first order and pseudo-second order kinetic were applied successfully to describe the adsorption kinetics (R² > 0.95). The isotherms can be defined by both Langmuir and Freundlich models, showing that ammonium removal by biochars is a complex process. BCFH-NaOH showed better performance, with the maximum adsorption capacity reaching 9.97 mg-NH₄/g, compared to 6.64 mg-NH₄/g of BCFH. Finally, BCFH-NaOH was tested with a practical groundwater sample (C₀ = 11.5 mg-NH₄/L), achieving a sorption efficiency of up to 80 % while eliminating most of the hardness. These results show that the modified coffee husk biochar could be applied as a low-cost, environmentally friendly adsorbent for ammonium removal.